Pre-harvest strategy for reducing aflatoxin accumulation during storage of maize in Argentina - Alaniz Zanon, María Silvina (2022)
Maize (Zea mays L.) is an important crop in Argentina. Aspergillus flavus may infect this crop at growing stage and the harvested kernels can be contaminated with aflatoxins (AFs), whose levels may increase during storage. In Argentina, silo bags, a hermetic type of storage system, are widely used. Biocontrol based on competitive exclusion by atoxigenic A. flavus strains is a useful tool for AFs management at pre-harvest stage. The aim of the present study was to evaluate the effect of pre-harvest biocontrol treatments on aflatoxin B1 (AFB1) accumulation in maize stored in silo bags during 3 and 6 months. Three bioformulations based on A. flavus AFCHG2 and ARG5/30 strains were applied during field trials as single and mixed inocula. Harvested kernels were stored in non-hermetic and hermetic silo bags. At initial time (t0), 3 and 6 months (t3 and t6) the following parameters were evaluated: percentage of damaged kernels, moisture content, water activity, Aspergillus section Flavi incidence, relative humidity, O2 and CO2 levels into the silo bags, and AFB1 levels. The biocontrol strains included in the 3 bioformulations were able to infect maize kernels during the field trial and displaced native toxigenic isolates. At t0 control plots showed 10.9 ± 0.4 μg/kg of AFB1 while no AFs were detected in all the treatments. Along the storage assay AFB1 levels varied from not detected (<1 μg/kg) to 20.1 ± 0.8 μg/kg. Hermetic bags were better than non-hermetic bags in preventing AFB1 accumulation. Both single and mixed inocula were effective to control AFB1 accumulation in maize kernels during 3 and 6 months. AFB1 was not detected in kernels from the treatment at field stage with AFCHG2 + ARG5/30 after 6 months of storage into hermetic bags. The application of the biocontrol agents at field stage is an appropriate tool to reduce AFB1 accumulation under storage in hermetic silo bags. This is the first report on biocontrol strategy based on native atoxigenic strains applied at pre-harvest stage to reduce AFB1 accumulation during storage in Argentina.